1953
DOI: 10.1182/blood.v8.2.101.101
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thromboplastin Component (PTC) A Hitherto Unrecognized Blood Coagulation Factor Case Report of PTC Deficiency

Abstract: 1. A new hemorrhagic disease characterized by a prolonged whole blood coagulation time caused by the delayed formation of thrombin is described. 2. The patient suffering from this disease was found to have normal concentrations of all previously described coagulation factors. 3. Because the coagulation defect could be completely corrected by the addition of tissue thromboplastin or platelet-poor hemophilic plasma and because tests for prothrombin and prothrombin conversion acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1954
1954
1967
1967

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…There are no other reliable studies in the literature regarding the disappearance rate of factor IX, although, since the original description of the severe congenital deficiency of this factor, the prolonged effect of transfusion on clotting time and other coagulation parameters has been noted.s. 98 Factor X: Graham41 studied the disappearance rate of factor X in a patient with severe congenital deficiency of this factor. Although there was considerable scatter of the points, the disappearance rate of factor X, studied over a period of five days, appeared to be a single exponential function with a half-life of approximately 47 hours.+…”
Section: In Vitro Survival Of Platelets and Clotting Factorsmentioning
confidence: 99%
“…There are no other reliable studies in the literature regarding the disappearance rate of factor IX, although, since the original description of the severe congenital deficiency of this factor, the prolonged effect of transfusion on clotting time and other coagulation parameters has been noted.s. 98 Factor X: Graham41 studied the disappearance rate of factor X in a patient with severe congenital deficiency of this factor. Although there was considerable scatter of the points, the disappearance rate of factor X, studied over a period of five days, appeared to be a single exponential function with a half-life of approximately 47 hours.+…”
Section: In Vitro Survival Of Platelets and Clotting Factorsmentioning
confidence: 99%
“…This reagent was prepared from normal serum by the method of White, Aggeler and Glendening (1953). The Factor-VII activity of the serum is destroyed by exposing the serum to a pH of 2.9 for 2 hours.…”
Section: 'Purijied' Christmas Factormentioning
confidence: 99%
“…The practical difficulties are the loss of the red cells to the transfusion service, loss of Factor VIII, and technical difficulty in obtaining a satisfactory yield of serum. White, Aggeler and Glendening (1953) reported that a potent preparation of Factor IX could be made from serum by adsorption with BaSO, from which the factor was eluted with citrate but this preparation was 'unsuitable for intravenous administration in the human subject'. For a time the Paris group made a therapeutic fraction from serum which they called CSB (Soulier, Blatrix, Prou-Wartelle and Vignal, 1962) by a method similar to that which they use for plasma, but this separate preparation has now been discontinued.…”
mentioning
confidence: 99%